Fluorine-containing polymer, preparation method thereof and ion exchange membrane

Preparation of fluoropolymers by solid phase/melt method solves the problems of complex preparation process and high cost in the prior art, and realizes the preparation of highly efficient and environmentally friendly sulfonimide functionalized polymers, which are suitable for high-temperature electrochemical applications. .

CN119219809APending Publication Date: 2024-12-31FOSHAN LVDONG HYDROGEN ENERGY TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411533079.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, perfluoro-backbone sulfonimide functionalized polymer has excellent electrochemical performance at high temperatures, but the preparation process has low polymerization rate of polar monomers, strong corrosiveness of reactants, harsh reaction conditions, and high pollution. , high cost and complex steps.

Method used

Fluoropolymers are prepared by solid phase/melting method. By reacting polymer raw materials, organic alkalis and functionalized reagents under solid phase/melting conditions, the reaction time is shortened, solvent consumption is reduced, operation is simplified and production costs are reduced.

Benefits of technology

It has achieved shortening of reaction time, reducing solvent consumption, simplification of operation and improving production efficiency, and is suitable for fields such as proton exchange membranes and fuel cell membrane electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219809A_ABST
    Figure CN119219809A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a fluorine-containing polymer, a preparation method thereof and an ion exchange membrane. The invention provides a preparation method of a fluorine-containing polymer, which comprises the following steps: (1) mixing a polymer raw material, an organic alkali, a functionalization reagent and an auxiliary agent, and reacting through a solid phase / melting method to obtain a crude product; and (2) cleaning the crude product by using water and / or an organic solvent, and then drying. The fluorine-containing polymer is prepared by adopting a solid phase / melting method, the solid phase / melting method has the advantages of short reaction time and low solvent consumption, and the product after the reaction is solid, so that the production cost can be reduced, and the preparation efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a fluorine-containing polymer and a preparation method thereof and an ion exchange membrane. Background Art

[0002] Perfluorosulfonic acid resin and its membrane materials have been widely used in fuel cell proton exchange membrane and membrane electrode, chlor-alkali industrial diaphragm, flow battery diaphragm, water electrolysis hydrogen production proton exchange membrane and other fields. One direction of improvement of perfluorosulfonic acid resin proton exchange membrane is to increase its operating temperature range. Taking fuel cells as an example, the common operating temperature of perfluorosulfonic acid resin proton exchange membrane is 60-80°C. If the operating temperature is further increased, the proton exchange membrane will lose water at high temperature, resulting in a decrease in electrochemical performance, thereby reducing the output power of the fuel cell. Sulfonimide functional groups have excellent gas-phase acidity. Sulfonimide functionalized polymers have the advantages of good thermal stability and strong proton transfer capacity. Compared with sulfonic acid functionalized polymers, they have better electrochemical properties at high temperatures. The existing technology prepares sulfonimide functionalized polymers by two methods: monomer copolymerization and grafting modification.

[0003] The advantage of fluorinated polymers obtained by monomer copolymerization is that the product structure is clear, but the synthesis conditions are harsh, the reactivity rate of strongly acidic comonomers is low, and the reaction system is severely corrosive. Another method is to react the functionalized reagent with the sulfonyl fluoride resin or sulfonamide resin with a perfluorinated main chain in a solvent. The production method of the sulfonyl fluoride resin with a perfluorinated main chain is mature, the copolymerization composition is controllable, and the fluorinated polymer with a suitable molecular weight and ion exchange equivalent can be obtained after modification. The sulfonamide resin with a perfluorinated main chain is obtained by reacting the sulfonyl fluoride resin with ammonia at low temperature. Compared with the sulfonyl fluoride resin, the sulfonamide resin is easier to disperse in the solvent, and some sulfonamide resins can be evenly dispersed in non-protonic polar solvents such as dimethyl sulfoxide and N,N-dimethylformamide. However, the sulfonyl fluoride resin with a perfluorinated main chain suitable for ion exchange membrane materials cannot be completely dissolved in fluorocarbon solvents. During the grafting process, a considerable part of the sulfonyl fluoride resin reacts with the functionalized reagent in a swollen state, which may cause incomplete reaction of the sulfonyl fluoride group. The preparation of sulfonyl imide functionalized polymers by reacting sulfonyl fluoride resins and sulfonamide resins with perfluorinated main chains with functionalized reagents in solvents will generate a large amount of fluorine-containing organic waste liquid, aggravating environmental pollution and production costs, and making post-treatment more complicated.

[0004] Therefore, a simpler and more environmentally friendly method is needed to prepare sulfonyl imide functionalized polymers and further apply such polymers in the fields of proton exchange membranes, fuel cell membrane electrodes, etc. Summary of the invention

[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems:

[0006] In the prior art, sulfonyl imide functionalized polymers with perfluorinated main chains have excellent electrochemical properties at high temperatures. The method of preparing polymers with sulfonyl imide groups as side chains by monomer copolymerization has the problems of low reactivity of polar monomers, strong corrosiveness of reactants and harsh reaction conditions. The method of polymer grafting modification in solution has the disadvantages of large pollution in the preparation process, high cost, complicated steps and long reaction time. The side chain end groups of some sulfonyl imide functionalized polymers with perfluorinated main chains are phenyl groups, and the chemical stability needs to be further improved.

[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, an embodiment of the present invention provides a method for preparing a fluorine-containing polymer, which adopts a solid phase / melting method to prepare the fluorine-containing polymer, which can shorten the reaction time and consume less organic solvent during the preparation process.

[0008] The method for preparing the fluorine-containing polymer according to the embodiment of the present invention comprises the following steps:

[0009] (1) mixing a polymer raw material, an organic base, a functionalizing agent and an auxiliary agent, and preparing a crude product by a solid phase / melt reaction;

[0010] (2) The crude product obtained in step (1) is washed with water and / or an organic solvent, and then dried.

[0011] The advantages and technical effects brought by the preparation method of the fluorine-containing polymer of the embodiment of the present invention are as follows: 1. The method of the embodiment of the present invention adopts a solid phase / melt method to allow the polymer raw material, organic base, and functionalizing agent to undergo a contact reaction, which can shorten the reaction time and reduce the solvent consumption in the preparation process; 2. The method of the embodiment of the present invention is simple to operate, the reaction conditions are not harsh, the post-processing method is simple, the production efficiency is high and the cost is low, and it is easy to promote and apply in industrial production.

[0012] In some embodiments, in step (1), when the polymer raw material is a sulfonyl halide resin and the functionalizing agent is a sulfonamide compound, the reaction formula is as shown in Formula 1:

[0013]

[0014] When the polymer raw material is a sulfonamide resin and the functionalizing agent is a sulfonyl halide compound, the reaction formula is as shown in Formula 2:

[0015]

[0016] In Formula 1 and / or Formula 2, a=a positive integer of 0 to 6, b=a positive integer of 2 to 5, x=2 to 10, y=1 to 10000; X is F, Cl, Br or I;

[0017] Q is selected from Or -R7, wherein R1 is selected from alkylene, fluoroalkylene or direct bond; R2, R3, R4, R5 and R6 are each independently selected from H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, nitrile; R7 includes at least one of alkyl, cycloalkyl, fluoroalkyl, fluorocycloalkyl, phenylalkylene.

[0018] In some embodiments, in step (1), the organic base comprises at least one of an organic amine or a nitrogen heterocyclic compound that does not contain a nitrogen heterocyclic ring, the organic amine that does not contain a nitrogen heterocyclic ring comprises at least one of an organic amine that does not contain a nitrogen heterocyclic ring and is substituted with an alkyl group of C1 to C20 and / or an aryl group of C6 to C20; the nitrogen heterocyclic compound comprises at least one of pyridine, imidazole, pyrrole, piperidine or piperazine that is substituted with an alkyl group of C1 to C20 and / or an aryl group of C6 to C20;

[0019] And / or, the auxiliary agent includes at least one of a lubricant, an antioxidant, a release agent or an opening agent;

[0020] and / or, the mass ratio of the polymer raw material, the organic base, the functionalizing agent and the auxiliary agent is 100:1-200:1-200:0-10;

[0021] And / or, the solid phase / melt method is any one of mixing first and then performing melt extrusion reaction, reaction molding in a flat vulcanizer, in-situ mixing reaction in an extruder, in-situ mixing reaction in an open mill, or in-situ mixing reaction in an internal mixer;

[0022] And / or, the temperature of the solid phase / melt process reaction is 100 to 340° C., and the time of the solid phase / melt process reaction is 1 to 300 min.

[0023] In some embodiments, the solid phase / melt method uses a single-screw extruder or a twin-screw extruder. In the screw extruder, the temperature of the feeding section is 60-180°C, the temperature of the melting section is 180-300°C, the temperature of the metering section is 200-300°C, and the temperature of the head and the die is 160-240°C.

[0024] In some embodiments, in step (2), the organic solvent comprises at least one of methanol, ethanol, isopropanol, n-propanol, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, acetone, butanone, n-hexane, cyclohexane or tetrahydrofuran;

[0025] And / or, the drying process includes at least one of freeze drying, forced air drying or vacuum drying.

[0026] In some embodiments, the preparation method further comprises the following steps:

[0027] (3) subjecting the fluorine-containing polymer obtained in step (2) to a transformation reaction in an alkaline solution to obtain an alkali metal-type fluorine-containing polymer;

[0028] (4) The fluorinated polymer in step (2) or the alkali metal type fluorinated polymer obtained in step (3) is subjected to ion replacement in an acid solution to obtain an acid type fluorinated polymer.

[0029] In some embodiments, in step (3), the alkaline solution includes at least one of a NaOH solution or a KOH solution, and the concentration of the alkaline solution is 0.1 to 8 mol / L;

[0030] And / or, in step (3), the temperature of the transformation reaction is 20 to 100°C, and the time of the transformation reaction is 1 to 48 hours.

[0031] And / or, in step (4), the acid solution comprises at least one of a hydrochloric acid solution or a sulfuric acid solution, and the concentration of the acid solution is 0.1 to 6 mol / L;

[0032] And / or, in the step (4), the temperature of the ion replacement is 20 to 100° C., and the time of the ion replacement is 1 to 48 hours.

[0033] The present invention also provides a fluorine-containing polymer, which is prepared by the above-mentioned preparation method.

[0034] In some embodiments, the fluoropolymer includes at least one of a first fluoropolymer or a second fluoropolymer;

[0035] The structure of the first fluorine-containing polymer is shown in Formula 3:

[0036]

[0037] The structure of the second fluorine-containing polymer is shown in Formula 4:

[0038]

[0039] In Formula 3 and / or Formula 4, R0 includes at least one of OM, F, Cl, Br, I or NH2, M is hydrogen, lithium, sodium, potassium, rubidium, cesium or other cations, and the other cations include at least one of ammonium ion, alkaline earth metal ion, iron ion, vanadium ion, titanium ion, silver ion, cerium ion, zinc ion and manganese ion;

[0040] a, b, x, y, R1, R2, R3, R4, R5, R6 and R7 are the same as those in Formula 1 or 2, and z is 0.01 to 1.

[0041] The embodiment of the present invention further provides an ion exchange membrane, comprising the fluorine-containing polymer obtained by the above preparation method or the above fluorine-containing polymer.

[0042] In some embodiments, the ion exchange membrane has a thickness of 5 to 450 μm;

[0043] and / or, the ion exchange capacity of the ion exchange membrane is 0.1 to 4 mmol / g;

[0044] And / or, the ion exchange membrane further comprises a reinforcement membrane, the reinforcement membrane is a porous membrane, and the material of the porous membrane comprises at least one of non-fluorinated polyolefin, fluorinated polymer material or aromatic polymer.

[0045] The present invention also provides a method for preparing an ion exchange membrane, comprising the following steps:

[0046] (a) dispersing a fluorine-containing polymer in a solvent to obtain a dispersion;

[0047] (b) forming and drying the dispersion obtained in step (a) to obtain an ion exchange membrane.

[0048] In some embodiments, in step (a), the solvent comprises at least one of water, a high boiling point organic solvent, tetrahydrofuran, and a lower aliphatic alcohol;

[0049] And / or, in the step (a), the dispersion temperature is 10 to 240° C., the dispersion time is 0.1 to 24 h, the dispersion pressure is normal pressure to 20 MPa, and the dispersion method includes at least one of stirring, shaking or ultrasound;

[0050] And / or, in the step (b), the forming comprises at least one of casting, pouring or coating;

[0051] And / or, in the step (b), the drying temperature is 20 to 180°C;

[0052] And / or, the step (b) further comprises: coating the dispersion on one side or both sides of the reinforcement layer, and drying to obtain the ion exchange membrane.

[0053] The embodiments of the present invention also provide the use of the above-mentioned ion exchange membrane or the ion exchange membrane prepared by the above-mentioned preparation method in batteries, chlor-alkali industry, water electrolysis hydrogen production, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 is the infrared spectra of PFNA-1, PFNA-7 and perfluorosulfonyl imide resin 4;

[0055] Figure 2 is the thermogravimetric curve of PFNA-7N;

[0056] Figure 3 are cross-sectional SEM images of PEM-7 and D-PEM-7;

[0057] Figure 4 It is the polarization curve diagram of PEM-7 and D-PEM-7. DETAILED DESCRIPTION

[0058] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0059] The method for preparing the fluorine-containing polymer according to the embodiment of the present invention comprises the following steps:

[0060] (1) mixing a polymer raw material, an organic base, a functionalizing agent and an auxiliary agent, and preparing a crude product by a solid phase / melt reaction;

[0061] (2) The crude product obtained in step (1) is washed with water and / or an organic solvent, and then dried.

[0062] The method for preparing the fluorine-containing polymer of the embodiment of the present invention adopts a solid phase / melt method to allow the polymer raw material, organic base, and functionalizing agent to contact and react, which can shorten the reaction time and reduce the solvent consumption in the preparation process; the method of the embodiment of the invention is simple to operate, the reaction conditions are not harsh, the post-processing method is simple, the production efficiency is high and the cost is low, which is convenient for promotion and application in industrial production.

[0063] In some embodiments, preferably, in step (1), when the polymer raw material is a sulfonyl halide resin and the functionalizing agent is a sulfonamide compound, the reaction formula is as shown in Formula 1:

[0064]

[0065] When the polymer raw material is a sulfonamide resin and the functionalizing agent is a sulfonyl halide compound, the reaction formula is shown in Formula 2:

[0066]

[0067] In Formula 1 and / or Formula 2, a=a positive integer of 0 to 6, b=a positive integer of 2 to 5, x=2 to 10, y=1 to 10000, 1 / (z+1)≥0.1%; X is F, Cl, Br or I;

[0068] Q is selected from Or -R7, wherein R1 is selected from alkylene, fluoroalkylene or direct bond; R2, R3, R4, R5 and R6 are each independently selected from H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, nitrile; R7 includes at least one of alkyl, cycloalkyl, fluoroalkyl, fluorocycloalkyl, phenylalkylene.

[0069] In some embodiments, preferably, the polymer raw material includes at least one of sulfonyl fluoride resin, sulfonyl chloride resin or sulfonamide resin. More preferably, the polymer raw material includes at least one of sulfonyl fluoride resin or sulfonamide resin. Sulfonamide resin is obtained by reacting sulfonyl halide resin with ammonia under low temperature conditions, which increases the reaction steps and costs, and is used to prepare fluorinated polymers. It will incur higher costs. The reactivity of sulfonyl chloride resin is higher than that of sulfonyl fluoride resin, but sulfonyl chloride resin needs to be prepared by reacting sulfonyl fluoride resin or perfluorosulfonic acid resin with an acyl chloride reagent. The reaction conditions are harsh, which increases the difficulty and cost of preparation. Sulfonyl fluoride resin has a complete industrial production capacity, mature and reliable melt processing technology, and good reactivity with small molecule sulfonamide compounds, and is the most preferred polymer raw material.

[0070] In some embodiments, preferably, the functionalizing agent comprises at least one of a sulfonamide compound, a sulfonyl chloride compound or a sulfonyl fluoride compound. More preferably, the functionalizing agent is a sulfonamide compound. The type of functionalizing agent depends on the chemical structure of the polymer raw material. Sulfonyl halide resin reacts with sulfonamide compound to obtain a fluorinated polymer, and sulfonamide resin reacts with sulfonyl halide compound to obtain a fluorinated polymer. Since sulfonyl fluoride resin is the most preferred polymer raw material, sulfonamide compound is the most preferred functionalizing agent.

[0071] In some embodiments, preferably, the sulfonamide compound includes 2-fluorobenzenesulfonamide, 3-fluorobenzenesulfonamide, 4-fluorobenzenesulfonamide, 2,3-difluorobenzenesulfonamide, 2,4-difluorobenzenesulfonamide, 2,5-difluorobenzenesulfonamide, 2,6-difluorobenzenesulfonamide, 3,4-difluorobenzenesulfonamide, 3,5-difluorobenzenesulfonamide, 2,3,4-trifluorobenzenesulfonamide, 2,3,5-trifluorobenzenesulfonamide, 2,4,5-trifluorobenzenesulfonamide, 2,3,6-trifluorobenzenesulfonamide, 2,4,6-trifluorobenzenesulfonamide, 3,4,5-trifluorobenzenesulfonamide, 2,3,5,6-tetrafluorobenzenesulfonamide, pentafluorobenzenesulfonamide, 2-(trifluorobenzenesulfonamide) 2-(Trifluoromethyl)benzenesulfonamide, 3-(trifluoromethyl)benzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide, 2,5-bis(trifluoromethyl)benzenesulfonamide, 3,5-bis(trifluoromethyl)benzenesulfonamide, o-methylbenzenesulfonamide, m-methylbenzenesulfonamide, p-methylbenzenesulfonamide, 2,6-dimethylbenzenesulfonamide, 3,5-dimethylbenzenesulfonamide, 2,4,6-trimethylbenzenesulfonamide, 3,4,5-trimethylbenzenesulfonamide, 2,3,5,6-tetramethylbenzenesulfonamide, 4-ethylbenzenesulfonamide, 4-propylbenzenesulfonamide, 4-tert-butylbenzenesulfonamide, 2,4,6-triisopropylbenzenesulfonamide, 2-naphthalenesulfonamide, 4-methyl-1-naphthalenesulfonyl amine, 5,6,7,8-tetrahydro-2-naphthalenesulfonamide, 4-biphenylsulfonamide, biphenyl-2-sulfonamide, 4′-fluorobiphenyl-4-sulfonamide, 2-cyanobenzenesulfonamide, 4-cyanobenzenesulfonamide, 2-fluoro-3-methylbenzenesulfonamide, 2-fluoro-4-methylbenzenesulfonamide, 2-fluoro-5-methylbenzenesulfonamide, 2-fluoro-5-cyanobenzenesulfonamide, 3-cyano-4-fluorobenzenesulfonamide, 4-fluoro-3-(trifluoromethyl)benzenesulfonamide, 4-fluoro-2-(trifluoromethyl)benzenesulfonamide, 5-fluoro-2-(trifluoromethyl)benzenesulfonamide, o-trifluoromethylbenzenesulfonamide, 3-(trifluoromethyl)benzenesulfonamide, 4-methylbenzenesulfonamide, 2- At least one of (1-naphthyl)ethanesulfonamide, (3-methylphenyl)methanesulfonamide, 2-phenyl-ethanesulfonamide, benzenesulfonamide, benzylsulfonamide, cyclopropanesulfonamide, 1-methylcyclopropanesulfonamide, cyclobutylsulfonamide, cyclopentanesulfonamide, cyclohexanesulfonamide, cyclohexylmethylsulfonamide, ethylsulfonamide, propylsulfonamide, tert-butylsulfonamide, n-pentanesulfonamide, 1-decanesulfonamide, 1-dodecanesulfonamide, trifluoromethylsulfonamide, pentafluoroethylsulfonamide, heptafluoropropylsulfonamide, perfluorobutylsulfonamide, perfluoro-n-hexylsulfonamide, perfluorooctanesulfonamide, 2,2,2-trifluoroethylsulfonamide, and perfluorohexylethylsulfonamide.Further preferably, the sulfonamide compounds include 2-fluorobenzenesulfonamide, 3-fluorobenzenesulfonamide, 4-fluorobenzenesulfonamide, 2,3-difluorobenzenesulfonamide, 2,4-difluorobenzenesulfonamide, 2,5-difluorobenzenesulfonamide, 2,6-difluorobenzenesulfonamide, 3,4-difluorobenzenesulfonamide, 3,5-difluorobenzenesulfonamide, 2,3,4-trifluorobenzenesulfonamide, 2,3,5-trifluorobenzenesulfonamide, 2,3,6-trifluorobenzenesulfonamide, 2,4,6-trifluorobenzenesulfonamide, 3,4,5-trifluorobenzenesulfonamide, 2,3,5,6-tetrafluorobenzenesulfonamide, pentafluorobenzenesulfonamide, 2-(trifluoromethyl)benzenesulfonamide, 3 -(trifluoromethyl)benzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide, 2,5-bis(trifluoromethyl)benzenesulfonamide, 3,5-bis(trifluoromethyl)benzenesulfonamide, 4-fluoro-3-(trifluoromethyl)benzenesulfonamide, 4-fluoro-2-(trifluoromethyl)benzenesulfonamide, 5-fluoro-2-(trifluoromethyl)benzenesulfonamide, o-trifluoromethylbenzylsulfonamide, 3-(trifluoromethyl)benzylsulfonamide, benzenesulfonamide, cyclopentanesulfonamide, cyclohexanesulfonamide, cyclohexylmethylsulfonamide, trifluoromethylsulfonamide, pentafluoroethylsulfonamide, perfluorobutylsulfonamide, perfluoro-n-hexylsulfonamide, perfluorohexylethylsulfonamide. More preferably, the sulfonamide compound includes at least one of 4-fluorobenzenesulfonamide, 4-(trifluoromethyl)benzenesulfonamide, pentafluorobenzenesulfonamide, o-trifluoromethylbenzylsulfonamide, benzenesulfonamide, cyclohexanesulfonamide, and perfluorohexylethylsulfonamide.

[0072] The sulfonamide group of the sulfonamide compound is replaced by a sulfonyl fluoride group to obtain a corresponding sulfonyl fluoride compound, for example, benzenesulfonamide corresponds to benzenesulfonyl fluoride, 3-fluorobenzenesulfonamide corresponds to 3-fluorobenzenesulfonyl fluoride, and perfluoro-n-hexylsulfonamide corresponds to perfluoro-n-hexylsulfonyl fluoride. The scope of the sulfonyl fluoride compound is consistent with the corresponding sulfonamide compound, which will not be repeated here. Further preferably, the sulfonyl fluoride compound includes at least one of 4-fluorobenzenesulfonyl fluoride, 4-(trifluoromethyl)benzenesulfonyl fluoride, pentafluorobenzenesulfonyl fluoride, o-trifluoromethylbenzylsulfonyl fluoride, benzenesulfonyl fluoride, cyclohexanesulfonyl fluoride, and perfluorohexylethylsulfonyl fluoride.

[0073] Replacing the sulfonamide group of the sulfonamide compound with a sulfonyl chloride group can obtain the corresponding sulfonyl chloride compound, for example, 5-fluoro-2-(trifluoromethyl)benzenesulfonamide corresponds to 5-fluoro-2-(trifluoromethyl)benzenesulfonyl chloride, o-trifluoromethylbenzylsulfonamide corresponds to o-trifluoromethylbenzylsulfonyl chloride, and perfluorohexylethylsulfonamide corresponds to perfluorohexylethylsulfonyl chloride. The scope of the sulfonyl chloride compound is consistent with the corresponding sulfonamide compound, which will not be repeated here. Further preferably, the sulfonyl chloride compound includes at least one of 4-fluorobenzenesulfonyl chloride, 4-(trifluoromethyl)benzenesulfonyl chloride, pentafluorobenzenesulfonyl chloride, o-trifluoromethylbenzylsulfonyl chloride, benzenesulfonyl chloride, cyclohexanesulfonyl chloride, and perfluorohexylethylsulfonyl chloride.

[0074] In some embodiments, preferably, in step (1), the organic base includes at least one of an organic amine or a nitrogen heterocyclic compound that does not contain a nitrogen heterocyclic ring, the organic amine that does not contain a nitrogen heterocyclic ring includes at least one of an organic amine that does not contain a nitrogen heterocyclic ring substituted with an alkyl group of C1 to C20 and / or an aryl group of C6 to C20; the nitrogen heterocyclic compound includes at least one of pyridine, imidazole, pyrrole, piperidine or piperazine that is substituted with an alkyl group of C1 to C20 and / or an aryl group of C6 to C20. Considering the efficiency of the reaction and the cost of the organic base, a tertiary amine is preferably used as the organic base of the reaction system. Further preferably, the organic base includes at least one of triethylamine, tripropylamine, triisopropylamine, tributylamine, tripentylamine, trihexylamine, triphenylamine, dodeca-tertiary amine, octadec-tertiary amine, N,N-dimethylcyclohexylamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dibutylethylenediamine, N,N-dimethylhexylamine, triethylethylenediamine, tetramethylethylenediamine, tetramethyl-1,3-propylenediamine, tetramethyl-1,6-hexanediamine, 2,5-dimethyl-p-phenylenediamine, N,N'-dibutylphenylenediamine, and N,N-dimethyldipropylenetriamine.

[0075] In some embodiments, preferably, in step (1), the auxiliary agent includes at least one of a lubricant, an antioxidant, a release agent or an opening agent.

[0076] In some embodiments, preferably, in the step (1), the mass ratio of the polymer raw material, the organic base, the functionalizing agent and the auxiliary agent is 100:1 to 200:1 to 200:0 to 10. Further preferably, the mass ratio is 100:5 to 150:5 to 150:0 to 8. More preferably, the mass ratio is 100:10 to 100:10 to 120:0 to 5. Too high content of organic base and functionalizing agent is not conducive to melt processing and produces unnecessary waste. Too low content means too little content of sulfonyl imide functional group. Other processing aids may or may not be added. For reaction systems with low melt index, a small amount of lubricant may be added to improve the fluidity of the reaction system.

[0077] In some embodiments, preferably, in the step (1), the solid phase / melting method is any one of mixing first and then performing melt extrusion reaction, reaction molding in a flat vulcanizer, in-situ mixing reaction in an extruder, in-situ mixing reaction in an open mill, or in-situ mixing reaction in an internal mixer. Preferably, the device used in the solid phase / melting method is an extruder, the pressure of the reaction system can reach more than 20MPa, the boiling point of the organic base and the functionalizing agent in the extruder is higher than the boiling point under standard atmospheric pressure, and the extrusion reaction can be carried out at a higher temperature. Further preferably, the solid phase / melting method uses a single screw extruder or a twin screw extruder, in which the temperature of the feeding section is 60-180°C, the temperature of the melting section is 180-300°C, the temperature of the metering section is 200-300°C, and the temperature of the die head and the die is 160-240°C. Appropriate temperature can ensure the fluidity and reaction rate of the reactants in the screw. The solid-phase / melt reaction mainly takes place in the melting section and the metering section. The temperature of these two sections is higher and the residence time is longer. The residence time at the head and the die is shorter, and the temperature of the feeding section is lower.

[0078] In some embodiments, in step (1), the crude product is an extrudate obtained by a solid phase / melt method, and the shape of the extrudate can be selected from pellets, wires, tubes, plates, rods or membranes. When the shape of the extrudate is a membrane, the crude product obtained is a first ion exchange membrane, and the fluorinated polymer described in step (2) is a second ion exchange membrane. Through the processing method of melt extrusion, not only can the fluorinated polymer be obtained, but also the ion exchange membrane can be directly extruded and molded, and further processing can obtain ion exchange membranes with different end groups and cations.

[0079] In some embodiments, preferably, in the step (1), the temperature of the solid phase / melt reaction is 100-340°C, and the time of the solid phase / melt reaction is 1-300 min. Further preferably, the temperature of the solid phase / melt reaction is 140-320°C, and the time of the solid phase / melt reaction is 2-200 min. More preferably, the temperature of the solid phase / melt reaction is 180-300°C, and the time of the solid phase / melt reaction is 5-120 min. The reaction temperature is adjusted according to the melting temperature of the polymer, and the reaction temperature is higher than the melting temperature of the polymer; the reaction time depends on the reaction temperature. When the same reaction degree is achieved, the reaction temperature is high, and the time required is short. Compared with the solvent reaction system, the solid phase / melt reaction temperature is higher, and has a faster reaction rate and a shorter reaction time.

[0080] In some embodiments, preferably, in step (2), the organic solvent comprises at least one of methanol, ethanol, isopropanol, n-propanol, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, acetone, butanone, n-hexane, cyclohexane or tetrahydrofuran. In the embodiment of the present invention, there is no need to specifically limit the solvent, as long as it can effectively disperse small molecule impurities such as functionalizing agents, organic bases, reaction by-products and other processing aids in the crude product and does not dissolve the fluorinated polymer.

[0081] In some embodiments, preferably, in the step (2), the drying process includes at least one of freeze drying, forced air drying or vacuum drying.

[0082] In some embodiments, preferably, the preparation method further comprises the following steps:

[0083] (3) subjecting the fluorine-containing polymer obtained in step (2) to a transformation reaction in an alkaline solution to obtain an alkali metal-type fluorine-containing polymer;

[0084] (4) The fluorinated polymer in step (2) or the alkali metal type fluorinated polymer obtained in step (3) is subjected to ion replacement in an acid solution to obtain an acid type fluorinated polymer.

[0085] The fluorinated polymer in step (2) contains unreacted sulfonyl halide functional groups or sulfonamide functional groups, and the ion exchange capacity of these two functional groups is negligible. For fluorinated polymers, increasing the content of ion exchange functional groups can improve the ion exchange capacity of the material. The sulfonyl halide functional groups and sulfonamide functional groups can react with alkali metal compounds in step (3) to be converted into sulfonic acid groups whose cations are alkali metal ions, and the sulfonamide groups can react with protonic acids in step (4) to be converted into sulfonic acid groups whose cations are hydrogen ions. The fluorinated polymer in step (2) can be directly used as an ion exchange resin in different scenarios. It is preferred to convert the sulfonyl fluoride and sulfonyl halide functional groups with weak ion exchange capacity into sulfonic acid functional groups to obtain ion exchange resins with higher ion exchange capacity. More preferably, the fluorine-containing polymer in step (2) contains unreacted sulfonyl halide functional groups, and an ion exchange resin with a high ion exchange capacity is obtained through step (3); the fluorine-containing polymer in step (2) contains unreacted sulfonamide functional groups, and an ion exchange resin with a high ion exchange capacity is obtained through steps (3) and / or (4).

[0086] In some embodiments, in addition to the sulfonyl imide functional groups formed by the reaction, the second ion exchange membrane in step (2) may also contain unreacted sulfonyl halide functional groups and sulfonamide functional groups. The sulfonyl halide functional groups and sulfonamide functional groups are converted into sulfonic acid functional groups that bind to alkali metal ions in step (3) to obtain a third ion exchange membrane. The sulfonyl halide functional groups do not react in step (4), and the sulfonamide functional groups are converted into sulfonic acid functional groups that bind to hydrogen ions in step (4) to obtain a fourth ion exchange membrane.

[0087] Since the ion exchange capacity of the sulfonyl fluoride functional group and the sulfonamide functional group is negligible, converting these two functional groups into sulfonic acid functional groups can improve the ion exchange capacity of the ion exchange membrane, and the conversion process is simple and efficient. The third ion exchange membrane and the fourth ion exchange membrane without sulfonyl halide functional groups are preferably used in fuel cells, water electrolysis to produce hydrogen, electrodialysis, liquid flow batteries, lithium ion battery polyelectrolytes and other fields.

[0088] In some embodiments, preferably, in step (3), the alkaline solution includes at least one of a NaOH solution or a KOH solution, and the concentration of the alkaline solution is 0.1 to 8 mol / L.

[0089] In some embodiments, preferably, in step (3), the temperature of the transformation reaction is 20 to 100°C, such as 20°C, 25°C, 30°C, 50°C, 100°C, etc.; and the time of the transformation reaction is 1 to 48h.

[0090] In some embodiments, preferably, in step (4), the acid solution includes at least one of a hydrochloric acid solution or a sulfuric acid solution, and the concentration of the acid solution is 0.1 to 6 mol / L.

[0091] In some embodiments, preferably, in the step (4), the temperature of the ion replacement is 20 to 100°C, such as 20°C, 25°C, 30°C, 50°C, 100°C, etc.; and the time of the ion replacement is 1 to 48 hours.

[0092] The embodiment of the present invention further provides a fluorine-containing polymer, which is prepared by the above-mentioned preparation method.

[0093] In some embodiments, preferably, the fluoropolymer includes at least one of a first fluoropolymer or a second fluoropolymer;

[0094] The structure of the first fluorine-containing polymer is shown in Formula 3:

[0095]

[0096] The structure of the second fluorine-containing polymer is shown in Formula 4:

[0097]

[0098] In Formula 3 and / or Formula 4, R0 includes at least one of OM, F, Cl, Br, I or NH2, M is hydrogen, lithium, sodium, potassium, rubidium, cesium or other cations, and the other cations include at least one of ammonium ion, alkaline earth metal ion, iron ion, vanadium ion, titanium ion, silver ion, cerium ion, zinc ion and manganese ion;

[0099] a, b, x, y, R1, R2, R3, R4, R5, R6 and R7 are the same as those in Formula 1 or 2, and z is 0.01 to 1.

[0100] x and z determine the ion exchange equivalent weight (EW) of the polymer and y determines the molecular weight of the polymer.

[0101] In some embodiments, preferably, x=2-10, further preferably, x=3-8, and more preferably, x=4-7.

[0102] In some embodiments, preferably, y=1-10000, further preferably, y=10-5000, more preferably, y=100-2000.

[0103] In some embodiments, preferably, z is 0.1-1, and more preferably, z is 0.9-1.

[0104] In some embodiments, preferably, the R1 is preferably selected from methylene, ethylene, propylene, butylene, perfluoromethylene, perfluoroethylene, CH(CH3) or a direct bond, more preferably selected from methylene or a direct bond;

[0105] The R2, R3, R4, R5 and R6 are each independently preferably selected from at least one of H, methyl, ethyl, n-propyl, cyclohexyl, isopropyl, n-butyl, tert-butyl, phenylene, phenyl, 4-fluorophenyl, 4-methylphenyl, trifluoromethyl, pentafluoroethyl and F; more preferably selected from at least one of methyl, isopropyl, tert-butyl, phenyl, trifluoromethyl and F; further preferably selected from at least one of trifluoromethyl or fluorine.

[0106] In some embodiments, preferably, the terminal structure of the first fluorinated polymer At least one selected from the following structures:

[0107]

[0108] Further preferred is at least one of 3-fluorophenyl, 4-fluorophenyl, 3,5-difluorophenyl, 2,6-difluorophenyl, 2,5-difluorophenyl, 2-(trifluoromethyl)phenyl, 2-fluoro-5-(trifluoromethyl)phenyl, 3-(trifluoromethyl)phenyl, 4-(trifluoromethyl)phenyl, 3,5-bis(trifluoromethyl)phenyl, 2,5-bis(trifluoromethyl)phenyl, 2,3,4,5,6-pentafluorophenyl, 2,4,6-trifluorophenyl, 2,3,5,6-tetrafluorophenyl. More preferably, at least one of 4-fluorophenyl, 4-(trifluoromethyl)phenyl, 2,3,4,5,6-pentafluorophenyl. Fluorinated substituents can significantly improve the chemical stability of fluorinated polymers. In terms of the positional distribution of substituents, symmetrical end groups have better chemical stability.

[0109] In some embodiments, preferably, the EW of the first fluoropolymer is 450 to 2000 g / mol. It is further preferably 600 to 1500 g / mol, and more preferably 700 to 1200 g / mol. If the EW is too high, the ion exchange capacity (IEC) of the material is low, the ion exchange capacity and ion transport capacity are poor, and the electrochemical performance applied to the proton exchange membrane or membrane electrode is poor; if the EW is too low, the water swelling of the material is difficult to control, and excessive water swelling will sharply reduce the dimensional stability and mechanical properties of the material.

[0110] In some embodiments, preferably, R7 in the second fluorine-containing polymer includes at least one of methyl, ethyl, tert-butyl, isopropyl, n-butyl, n-propyl, trifluoromethyl, perfluoroethyl, perfluoro-n-propyl, perfluoroisopropyl, perfluoro-n-butyl, perfluoro-tert-butyl, perfluoropentyl, perfluorohexyl, perfluoroheptyl, perfluorooctyl, perfluorohexylethyl, 2,2,2-trifluoroethyl, cyclopentyl, cyclopropyl, cyclohexyl, perfluorocyclohexyl, perfluoro-4-ethylcyclohexyl, benzyl, α-methylbenzyl, phenethyl, phenylpropyl, and phenylisopropyl. Further preferably, it includes at least one of cyclohexyl, trifluoromethyl, perfluoroethyl, perfluoropropyl, perfluorobutyl, perfluoroisopropyl, perfluoroisobutyl, perfluorohexyl, perfluorooctyl, perfluorohexylethyl, phenyl, benzyl, and cyclohexyl; more preferably, it is selected from the following structures:

[0111] Perfluoroalkyl groups have good chemical stability as terminal groups, and some fluoroalkyl groups, cyclohexyl groups and phenyl groups have good chemical stability.

[0112] The embodiment of the present invention also provides an ion exchange membrane, including the fluorine-containing polymer prepared by the above preparation method or the above fluorine-containing polymer. In the embodiment of the present invention, the sulfonimide functional group of the ion exchange membrane has the strongest gas phase acidity, improves the ion transmission capacity of the material at high temperature, can improve the proton conductivity of the ion exchange membrane, and is suitable for fuel cell ion exchange membranes, ion exchange membranes for water electrolysis, and flow battery diaphragms.

[0113] In some embodiments, preferably, the thickness of the ion exchange membrane is 5 to 450 μm, more preferably 6 to 300 μm, and even more preferably 7 to 200 μm.

[0114] In some embodiments, preferably, the capacity of the ion exchange membrane is 0.1 to 4 mmol / g, more preferably 0.15 to 2.5 mmol / g, and even more preferably 0.2 to 2.0 mmol / g.

[0115] In some embodiments, preferably, the ion exchange membrane further comprises a reinforcement membrane, the reinforcement membrane is a porous membrane, and the material of the porous membrane comprises at least one of non-fluorinated polyolefins, fluorinated polymer materials or aromatic polymers. Further preferably, the non-fluorinated polyolefin comprises at least one of polyethylene, polypropylene or ethylene-propylene copolymer; the fluorinated polymer material comprises at least one of polytetrafluoroethylene, tetrafluoroethylene hexafluoropropylene copolymer, tetrafluoroethylene propylene copolymer, ethylene tetrafluoroethylene copolymer, tetrafluoroethylene hexafluoropropylene ethylene copolymer, polyvinylidene fluoride, vinylidene fluoride hexafluoropropylene copolymer, tetrafluoroethylene perfluoroalkyl vinyl ether copolymer, vinylidene fluoride tetrafluoroethylene hexafluoropropylene copolymer, polyvinyl fluoride, polychlorotrifluoroethylene, ethylene chlorotrifluoroethylene copolymer; the aromatic polymer membrane comprises at least one of polyaryletherketone, polysulfone, polyethersulfone, polyethersulfoneketone, polybenzimidazole, polyaromatic amide, polyimide or polyetheretherketone.

[0116] The present invention also provides a method for preparing an ion exchange membrane, comprising the following steps:

[0117] (a) dispersing a fluorine-containing polymer in a solvent to obtain a dispersion;

[0118] (b) forming and drying the dispersion obtained in step (a) to obtain an ion exchange membrane.

[0119] In the embodiment of the present invention, an ion exchange membrane is obtained by solution molding and drying. The obtained ion exchange membrane has good flatness, uniform thickness distribution, and better performance; the process is simple, easy to operate, and has high production efficiency, which is convenient for wide application in industrial production. The dispersion in the preparation process can also be used to prepare coatings, hydrogels and adhesives for porous membranes such as desalination membranes and ultra / microfiltration membranes, as well as various fabrics and protective equipment such as surgical gloves, protective clothing, and sterile sheets, and has a wide range of applications.

[0120] In some embodiments, preferably, in step (a), the solvent comprises at least one of water, a high boiling point organic solvent, tetrahydrofuran, and a lower aliphatic alcohol. Further preferably, the high boiling point organic solvent comprises at least one of ethylene glycol, propylene glycol, glycerol, DMF, DMAc, DMSO, hexamethylphosphoric acid triamide, and NMP; and the lower aliphatic alcohol comprises at least one of methanol, ethanol, isopropanol, n-propanol, and n-butanol.

[0121] In some embodiments, preferably, in step (a), the dispersion temperature is 10-240° C., the dispersion time is 0.1-24 h, the dispersion pressure is normal pressure to 20 MPa, and the dispersion method includes at least one of stirring, shaking or ultrasound.

[0122] In some embodiments, preferably, in the step (b), the forming comprises at least one of casting, pouring or coating;

[0123] And / or, the drying temperature is 20 to 180°C;

[0124] And / or, it also includes: coating the dispersion on one side or both sides of the reinforcement layer, and drying to obtain the ion exchange membrane.

[0125] The embodiments of the present invention also provide the use of the above-mentioned ion exchange membrane or the ion exchange membrane prepared by the above-mentioned preparation method in batteries, chlor-alkali industry, water electrolysis hydrogen production, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.

[0126] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0127] Example 1

[0128] Weigh 100 parts (mass 0.4kg) of sulfonyl fluoride resin 1, and weigh a certain amount of functionalizing agent, processing aid and organic base. After preliminary mixing by stirring and shaking, add it to a single-screw extruder for extrusion reaction, and granulate it after extrusion to obtain solid particles. The solid particles are alternately washed with ethyl acetate, acetone and water to remove small molecular impurities, and then added to a 2mol / L sodium hydroxide solution, reacted at 90°C for 24h to convert the unreacted sulfonyl fluoride group into a sodium sulfonate group to obtain sodium-type fluoropolymer particles. Add the sodium-type fluoropolymer particles to a 0.5mol / L sulfuric acid solution, stir at 80°C for 2h to replace the sodium ions with hydrogen ions, wash them clean, and vacuum dry them at 45°C to obtain clean acid-type fluoropolymer particles.

[0129] The structural formula of sulfonyl fluoride resin 1 is:

[0130]

[0131] Table 1 shows the types and amounts of functionalizing agents, organic bases, and processing aids.

[0132] Table 2 shows the temperature and reaction time of each section of the extrusion equipment. The reaction time is the sum of the residence time of the reactants in the melting section and the homogenization section.

[0133] Table 3 shows the structural formula, grafting rate and EW of sodium-type and acid-type fluorinated polymers, where M' is Na or H.

[0134] Table 1

[0135]

[0136] Table 2

[0137]

[0138] Table 3

[0139]

[0140]

[0141] By adding a certain amount of functionalizing agent and organic base, melt extrusion reaction is carried out under appropriate reaction conditions. Sulfonyl fluoride resin has a certain self-lubricating ability, and the functionalizing agent and organic base are small molecular compounds with low liquid or melt viscosity, which are conducive to improving the fluidity of the reaction system, and no other processing aids can be added for extrusion reaction. For systems with less addition of functionalizing agent and organic base, a certain amount of processing aid can be added to improve processing performance. A suitable reaction system can make the grafting rate reach more than 99.9%, and the yield of acid-type fluorinated polymers in all reaction systems is not less than 95%.

[0142] Example 2

[0143] Sulfonyl fluoride resin 2 reacts with ammonia to obtain sulfonamide resin 2. 100 parts (0.2 kg) of sulfonamide resin 2, 40 parts of trihexylamine and a certain amount of functionalizing agent are weighed, preliminarily mixed, and then added to a twin-screw extruder for extrusion reaction, and granulated to obtain solid particles after extrusion. During the extrusion process, the temperature of the feeding section is 160-180°C; the temperature of the melting section is 245-255°C; the temperature of the metering section is 240-250°C; the temperature of the die head is 160-180°C; and the reaction time is 30 minutes.

[0144] The solid particles were washed alternately with ethyl acetate, acetone and water to remove small molecular impurities, added to a 2 mol / L hydrochloric acid solution, stirred at 60°C for 12 h to replace the sulfonamide groups with sulfonic acid groups, and after washing, vacuum dried at 45°C to obtain clean acid-type fluorinated polymer particles.

[0145] The structural formula of sulfonamide resin 2 is:

[0146]

[0147] Table 4

[0148]

[0149] The structural formula of PFNA-7 is:

[0150]

[0151] The structural formula of PFNA-8 is:

[0152]

[0153] The structural formula of PFNA-9 is:

[0154]

[0155] The reaction system composed of sulfonamide resin and sulfonyl halide compound can achieve a sulfonyl imide group grafting rate of more than 99.9% under appropriate reaction conditions, and the yield of acid-type fluorinated polymers in all reaction systems is not less than 95%. The conversion of sulfonamide resin from sulfonyl fluoride resin increases the preparation steps, but the cost of sulfonyl chloride chemical is much lower than that of sulfonamide compound, and the preferred reaction route should be considered from the overall cost of raw materials.

[0156] Figure 1 The infrared spectra of PFNA-1, PFNA-7 and perfluorosulfonyl imide resin 4 are shown in Figure 1. -1 、1050cm -1 、1055cm -1 The characteristic peak of SNS group is shown at 1082cm -1 、1086cm -1 The vibration peak of CF on the benzene ring is at 880 cm-1. -1 The out-of-plane bending vibration peak of CH on the benzene ring is at 1475 cm -1 The C=C vibration peak on the benzene ring of PFNA-1 is split at 1470 cm -1 and 1408cm -1 .

[0157] In the process of preparing PFNA-7, the unacidified intermediate product is named PFNA-7N. The terminal groups of the side chain of PFNA-7F are sulfonamide and perfluorophenyl, which has good thermal stability. Figure 2 This is the thermogravimetric curve of PFNA-7N polymer. There are multiple inflection points in the thermal decomposition process of the polymer: when the decomposition temperature is 223°C, the crystalline water in the polymer is completely decomposed; when the decomposition temperature is 393°C, the side chain structure of the polymer begins to decompose; the maximum decomposition rate temperature of the polymer is 477°C. The thermal stability of PFNA-7N meets the requirements for functionalization reaction and extrusion molding by melt extrusion. The sulfonamide functional group, sulfonyl fluoride functional group and sulfonimide functional group all have good thermal stability, which meets the requirements for melt extrusion reaction and melt extrusion molding.

[0158] Example 3

[0159] Weigh 5g of sulfonyl fluoride resin 1 in Example 1, mix with 1g of trifluoromethylbenzylsulfonamide and 4g of tributylamine, and in a flat vulcanizer, the upper and lower mold temperatures are both 210°C, the reaction time is 2h, and a melt reaction product sample is obtained. The product sample is further treated with reference to the sodium and acidification methods in Example 1 to obtain an acid-type fluorinated polymer PFNA-10. The EW of PFNA-10 is 1086g / mol, the grafting rate is 26.3%, and the structural formula is:

[0160]

[0161] Example 4

[0162] Different from Example 3, the functionalizing agent is 2,3,4,5,6-pentafluorobenzenesulfonamide, the organic base is trihexylamine, the upper and lower mold temperatures of the flat vulcanizer are both 280°C, and other conditions are the same to obtain the acid-type fluorinated polymer PFNA-11. The EW of PFNA-11 is 1087 g / mol, and the grafting rate is 22.7%.

[0163] Example 5

[0164] Weigh 5g of sulfonamide resin 2 in Example 2, mix with 1g of cyclohexanesulfonyl chloride and 4g of tributylamine, and in a flat vulcanizer, the upper and lower mold temperatures are both 200°C, the reaction time is 2h, and a melt reaction product sample is obtained. The product sample is further treated with reference to the acidification method in Example 2 to obtain an acid-type fluorinated polymer PFNA-12. The EW of PFNA-12 is 841g / mol, the grafting rate is 27.0%, and the structural formula is:

[0165]

[0166] Example 6

[0167] The difference from Example 5 is that the functionalizing agent is 1 g of perfluorohexyl ethylsulfonyl chloride, the reaction time is 12 h, and other conditions are the same to obtain the acid-type fluorinated polymer PFNA-13. The EW of PFNA-13 is 904 g / mol, the grafting rate is 14.3%, and the structural formula is:

[0168]

[0169] Example 7

[0170] The difference from Example 5 is that the functionalizing agent is 5 g of benzenesulfonyl fluoride, and the other conditions are the same, to obtain the acid-type fluorinated polymer PFNA-14. The EW of PFNA-14 is 924 g / mol, and the grafting rate is 88.0%.

[0171] Example 8

[0172] Weigh 25g of sulfonamide resin 2 in Example 2, mix with 25g of 2,3,5,6-tetramethylbenzenesulfonyl chloride and 20g of trihexylamine, and in a flat vulcanizer, the upper and lower mold temperatures are both 280°C, the reaction time is 2h, and a melt reaction product sample is obtained. The product sample is further treated with reference to the acidification method in Example 2 to obtain an acid-type fluorinated polymer PFNA-15. The EW of PFNA-15 is 962g / mol and the grafting rate is 82.0%. The structural formula is:

[0173]

[0174] Example 9

[0175] Weigh 100 parts (mass 0.5 kg) of a mixture of sulfonyl fluoride resin 3, 50 parts of 4-fluorobenzenesulfonamide, 40 parts of trihexylamine and 2 parts of stearyl alcohol, stir and mix, add to a single screw extruder for extrusion reaction, and roll to form a film after extrusion to obtain film material A. During the extrusion molding process, the temperature of the feeding section is 170-190°C; the temperature of the melting section is 240-250°C; the temperature of the metering section is 240-250°C; the temperature of the die head is 200-210°C; the reaction time is 30 min; and the average thickness of the extruded film material A is 100 μm.

[0176] The membrane material A was washed alternately with acetone and ethyl acetate to obtain an ion exchange membrane PEM-100F. The IEC of PEM-100F was 1.04 mmol / g.

[0177] PEM-100F was immersed in 8 mol / L sodium hydroxide solution and reacted at 80°C for 4 h to convert the unreacted sulfonyl fluoride groups into sodium sulfonate groups to obtain the sodium-type ion exchange membrane PEM-100Na.

[0178] PEM-100Na was immersed in 2 mol / L sulfuric acid solution and reacted at 90°C for 12 hours to replace sodium ions with hydrogen ions to obtain proton exchange membrane PEM-100H. The grafting rate of fluorinated polymer in PEM-100H was 90.9% and IEC was 1.16 mmol / g.

[0179] The structural formula of sulfonyl fluoride resin 3 is:

[0180]

[0181] Example 10

[0182] Different from Example 4, the functionalizing agent is benzenesulfonamide, the average thickness of the extruded film is 175 μm, and the proton exchange membrane PEM-175H is obtained. The grafting rate of the fluorine-containing polymer in PEM-100H is 94.9%, and the IEC is 1.17 mmol / g.

[0183] Embodiment 11

[0184] 1 g of the acidic PFNA-1 in Example 1 was weighed and dissolved in 9 mL of DMSO at 80° C., the dispersion was cast in an ultra-flat culture dish, and dried at 180° C. for 6 hours to obtain an ion exchange membrane PEM-5 with an average thickness of 50 μm.

[0185] Example 12

[0186] Weigh 15 g of the acid-type PFNA-5 in Example 1 and dissolve it in 85 g of a hydroalcohol solvent (water: ethanol: isopropanol = 4:1:5 by mass) at 60°C to obtain a dispersion. Slit-coat the dispersion on both sides of the ePTFE-2, dry at 90°C for 3 min, and heat treat at 180°C for 10 min to obtain an ion exchange membrane PEM-5 with an average thickness of 12 μm.

[0187] Embodiment 13

[0188] The difference from Example 2 is that the fluorine-containing polymer used to prepare the ion exchange membrane is PFNA-7 in Example 2, and other conditions remain unchanged, so that an ion exchange membrane PEM-7 with an average thickness of 12 μm is obtained.

[0189] Embodiment 14

[0190] Weigh 10g of PFNA-9 in Example 2 and dissolve it in 40g of water-alcohol mixed solvent (water, ethanol, n-propanol, isopropanol, n-butanol mass ratio is 2:1:1:1:1) at 30°C to obtain a resin dispersion. Apply it on both sides of ePTFE-1 with a doctor blade, dry it at 110°C for 3min, and heat treat it at 160°C for 15min to obtain an ion exchange membrane PEM-9 with an average thickness of 5μm. The IEC of PEM-9 is 0.78mmol / g.

[0191] Embodiment 15

[0192] Weigh 25g of the acidic PFNA-4 in Example 1 and dissolve it in a mixed solvent (the mass ratio of water, ethanol and DMF is 1:2:1) at 80°C to obtain a resin dispersion. Apply it on both sides of the ePTFE-1 with a doctor blade, dry it at 110°C for 3min, and heat treat it at 160°C for 15min to obtain an ion exchange membrane PEM-4 with an average thickness of 25μm. The IEC of PEM-4 is 0.82mmol / g.

[0193] Comparative Example 1

[0194] Different from Example 9, no functionalizing agent and organic base were added during melt extrusion, and a proton exchange membrane D-PEM-100H was obtained.

[0195] Comparative Example 2

[0196] Different from Example 10, no functionalizing agent and organic base were added during melt extrusion, and a proton exchange membrane D-PEM-175H was obtained.

[0197] Comparative Example 3

[0198] Weigh 1g of perfluorosulfonic acid resin 1 and dissolve it in 9mL of DMSO at 80℃, cast the dispersion in an ultra-flat petri dish, and dry it at 180℃ for 6 hours to obtain an ion exchange membrane D-PEM-1 with an average thickness of 50μm. Perfluorosulfonic acid resin 1 is transformed from sulfonyl fluoride resin 1, and its structural formula is:

[0199]

[0200] Comparative Example 4

[0201] The difference from Example 12 is that the polymer used to prepare the ion exchange membrane is D-PFNA-6, and other conditions remain unchanged, thereby obtaining an ion exchange membrane D-PEM-5 with an average thickness of 12 μm.

[0202] D-PFNA-6 has the same structural formula as PFNA-6 and is prepared by reacting a sulfonyl fluoride resin and a functionalizing agent in a solvent. The preparation method is: under a nitrogen atmosphere, add 150g of dioxane and then add 10g of the sulfonyl fluoride resin 1 in Example 1 and 7.5g of benzenesulfonamide, and stir and mix; slowly drop 60g of triethylamine, and the temperature rises to 80°C during the dropwise addition process. After 48 hours of reaction, stop the reaction, filter to obtain the resin, wash the product, and dry it. The product is sodiumized and acidified according to the method in Example 1, and dried to obtain the acid-type fluorinated polymer D-PFNA-6. The EW and grafting rate of D-PFNA-6 are basically the same as those of PFNA-6, and the yield is 73%.

[0203] Comparative Example 5

[0204] The difference from Example 13 is that the polymer used to prepare the ion exchange membrane is perfluorosulfonic acid resin 2, and other conditions remain unchanged to obtain an ion exchange membrane D-PEM-7 with an average thickness of 12 μm. Perfluorosulfonic acid resin 2 is obtained by transforming sulfonyl fluoride resin 2, and its structural formula is:

[0205]

[0206] Comparative Example 6

[0207] Perfluorosulfonyl imide resin 4 is prepared by free radical copolymerization of perfluorosulfonyl imide vinyl ether monomer and tetrafluoroethylene monomer. Specifically, perfluorosulfonyl imide vinyl ether monomer and tetrafluoroethylene monomer (TFE) are continuously copolymerized in disodium hydrogen phosphate / sodium dihydrogen phosphate buffer using ammonium persulfate (0.3126 g) / sodium bisulfite (0.2838 g) as initiators.

[0208] First, 2.97g of disodium hydrogen phosphate heptahydrate and 0.2838g of sodium dihydrogen phosphate were fully dissolved in 260mL of deionized water after degassing to prepare a first solution; then, 4.169g of perfluorosulfonyl imide vinyl ether monomer was added to the first solution, and the solution was cooled to 8°C under a nitrogen atmosphere to prepare a second solution. The autoclave was evacuated, and the initiator was added to the second solution after being purged with nitrogen three times within 5 minutes; the second solution with the added initiator was degassed with helium for more than 20 minutes; the solution was sucked into a completely evacuated autoclave, and an appropriate amount of degassed deionized water was added so that the volume of the solution was half of that of the reactor. When the reactor temperature reaches 10°C, TFE is added until the pressure reaches 150 psi and the pressure is maintained at 145-150 psi by adding TFE throughout the process; finally, the filtrate is acidified with 12 mol / L hydrochloric acid (200 mL) to obtain a precipitated polymer, the polymer is washed with water until the water is neutral and the pH value is 6.5-7.5, and vacuum dried at 50°C for 24 h to obtain perfluorosulfonyl imide resin 4.

[0209] The EW of perfluorosulfonyl imide resin 4 is 1200 g / mol, and the structural formula is:

[0210]

[0211] Table 5 shows the tensile strength and conductivity in water (80°C and 95°C) of the proton exchange membranes prepared by melt extrusion in Example 9, Example 10, Comparative Example 1 and Comparative Example 2. Under 80°C, the conductivity of PEM-100H and D-PEM-100H is similar. When the temperature is increased to 95°C, the conductivity of PEM-100H is further improved, but the conductivity of D-PEM-100H decreases due to water loss at high temperature. The sulfonimide functional group exhibits better electrochemical properties at high temperatures. The tensile strength of PEM-100H is higher than that of D-PEM-100H, which may be because the longer side chain structure of the former is conducive to the formation of a phase separation structure, and the benzene ring structure of the terminal group improves the rigidity of the material.

[0212] Table 5

[0213]

[0214] Table 6 shows the tensile strength and conductivity of the solution-formed ion exchange membranes in Example 11 and Comparative Example 3 at different relative humidities. The test temperature of the conductivity is 80° C., and the relative humidity is 50% and 90% respectively.

[0215] Table 6

[0216]

[0217] The ion exchange membrane was prepared by solution molding. The conductivity of PEM-1 was similar to that of D-PEM-1 under high humidity conditions. At low humidity of 50% RH, the electrochemical performance of PEM-1 was significantly better than that of D-PEM-1. The long side chains and rigid end groups also improved the mechanical properties of PEM-1, which had higher tensile strength and was beneficial to the mechanical durability of the ion exchange membrane.

[0218] Table 7 shows the IEC, water absorption, tensile strength and tensile modulus of the ion exchange membranes containing the reinforcement layer in Example 12, Example 13, Comparative Example 4 and Comparative Example 5. Table 8 shows the free radical resistance and the conductivity under different relative humidity. The test temperature of the conductivity is 80° C., and the relative humidity is 40% and 95%, respectively.

[0219] Table 7

[0220]

[0221] Table 8

[0222]

[0223] Compared with D-PEM-5, PEM-5 has similar IEC, water absorption and conductivity under different humidity conditions, but PEM-5 has better mechanical properties and chemical durability. This is because the phenyl group on the fluoropolymer side chain in PEM-5 contains a trifluoromethyl substituent. This perfluoroalkyl substituent can improve the material's free radical resistance and mechanical properties.

[0224] Compared with PEM-7 and D-PEM-7, the main chain structure of the two is the same. Due to the difference in the side chain structure, PEM-7 has lower IEC, water absorption, and higher tensile strength and tensile modulus. The lower water absorption gives PEM-7 better dimensional stability, and the higher mechanical properties can improve the mechanical durability of the membrane material. At the same time, the fluorinated polymer of PEM-7 is a perfluorinated structure, and the end group of the side chain is a perfluorophenyl group with large steric hindrance, so it exhibits good resistance to free radicals. Although the IEC of PEM-7 is lower than that of D-PEM-7, the conductivity of the two is similar at high humidity. At low humidity, the proton transport characteristics of the sulfonimide group make the conductivity of PEM-7 better than that of D-PEM-7, which is more suitable for the actual working conditions of fuel cells.

[0225] Figure 3 The following are SEM images of the cross sections of PEM-7 and D-PEM-7. Both materials have good filling effect in the reinforcement layer.

[0226] Figure 4 The polarization curves of PEM-7 and D-PEM-7 fuel cell cells. At 80°C and 30% RH, the power density of the membrane electrode prepared by PEM-7 reaches 1175mW / cm 2 @0.65V, better than D-PEM-7’s 981mW / cm 2 @0.65V, and has lower internal resistance and better fuel cell single cell performance.

[0227] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0228] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a fluorine-containing polymer, characterized in that: The following steps are involved: (1) mixing a polymer raw material, an organic base, a functionalizing agent and an auxiliary agent, and preparing a crude product by a solid phase / melt reaction; (2) The crude product obtained in step (1) is washed with water and / or an organic solvent, and then dried.

2. The method for preparing a fluorine-containing polymer according to claim 1, characterized in that: In the step (1), when the polymer raw material is a sulfonyl halide resin and the functionalizing agent is a sulfonamide compound, the reaction formula is as shown in Formula 1: When the polymer raw material is a sulfonamide resin and the functionalizing agent is a sulfonyl halide compound, the reaction formula is as shown in Formula 2: In Formula 1 and / or Formula 2, a=a positive integer of 0 to 6, b=a positive integer of 2 to 5, x=2 to 10, y=1 to 10000; X is F, Cl, Br or I; Q is selected from Or -R7, wherein R1 is selected from alkylene, fluoroalkylene or direct bond; R2, R3, R4, R5 and R6 are each independently selected from H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, nitrile; R7 includes at least one of alkyl, cycloalkyl, fluoroalkyl, fluorocycloalkyl, phenylalkylene.

3. The method for preparing a fluorine-containing polymer according to claim 1, characterized in that: In the step (1), the organic base comprises at least one of an organic amine or a nitrogen heterocyclic compound that does not contain a nitrogen heterocyclic ring, the organic amine that does not contain a nitrogen heterocyclic ring comprises at least one of an organic amine that does not contain a nitrogen heterocyclic ring and is substituted with a C1-C20 alkyl group and / or a C6-C20 aryl group; the nitrogen heterocyclic compound comprises at least one of pyridine, imidazole, pyrrole, piperidine or piperazine that is substituted with a C1-C20 alkyl group and / or a C6-C20 aryl group; And / or, the auxiliary agent includes at least one of a lubricant, an antioxidant, a release agent or an opening agent; and / or, the mass ratio of the polymer raw material, the organic base, the functionalizing agent and the auxiliary agent is 100:1-200:1-200:0-10; And / or, the solid phase / melt method is any one of mixing first and then performing melt extrusion reaction, reaction molding in a flat vulcanizer, in-situ mixing reaction in an extruder, in-situ mixing reaction in an open mill, or in-situ mixing reaction in an internal mixer; And / or, the temperature of the solid phase / melt process reaction is 100 to 340° C., and the time of the solid phase / melt process reaction is 1 to 300 min.

4. The method for preparing a fluorine-containing polymer according to claim 3, characterized in that: The solid phase / melting method adopts a single screw extruder or a twin screw extruder. In the screw extruder, the temperature of the feeding section is 60-180°C, the temperature of the melting section is 180-300°C, the temperature of the metering section is 200-300°C, and the temperature of the die head and the die is 160-240°C.

5. The method for preparing a fluorine-containing polymer according to claim 1, characterized in that: In the step (2), the organic solvent comprises at least one of methanol, ethanol, isopropanol, n-propanol, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, acetone, butanone, n-hexane, cyclohexane or tetrahydrofuran; And / or, the drying process includes at least one of freeze drying, forced air drying or vacuum drying.

6. The method for preparing a fluorine-containing compound according to claim 1, characterized in that: The preparation method further comprises the following steps: (3) subjecting the fluorine-containing polymer obtained in step (2) to a transformation reaction in an alkaline solution to obtain an alkali metal-type fluorine-containing polymer; (4) The fluorinated polymer in step (2) or the alkali metal type fluorinated polymer obtained in step (3) is subjected to ion replacement in an acid solution to obtain an acid type fluorinated polymer.

7. The method for preparing a fluorine-containing polymer according to claim 6, characterized in that: In the step (3), the alkaline solution includes at least one of a NaOH solution or a KOH solution, and the concentration of the alkaline solution is 0.1 to 8 mol / L; And / or, in step (3), the temperature of the transformation reaction is 20 to 100° C., and the time of the transformation reaction is 1 to 48 hours; And / or, in step (4), the acid solution comprises at least one of a hydrochloric acid solution or a sulfuric acid solution, and the concentration of the acid solution is 0.1 to 6 mol / L; And / or, in the step (4), the temperature of the ion replacement is 20 to 100° C., and the time of the ion replacement is 1 to 48 hours.

8. A fluorine-containing polymer, characterized in that The preparation method is described in any one of claims 1 to 7.

9. The fluorine-containing polymer according to claim 8, characterized in that The fluoropolymer includes at least one of a first fluoropolymer or a second fluoropolymer; The structure of the first fluorine-containing polymer is shown in Formula 3: The structure of the second fluorine-containing polymer is shown in Formula 4: In Formula 3 and / or Formula 4, R0 includes at least one of OM, F, Cl, Br, I or NH2, M is hydrogen, lithium, sodium, potassium, rubidium, cesium or other cations, and the other cations include at least one of ammonium ion, alkaline earth metal ion, iron ion, vanadium ion, titanium ion, silver ion, cerium ion, zinc ion and manganese ion; a, b, x, y, R1, R2, R3, R4, R5, R6 and R7 are the same as those in Formula 1 or 2, and z is 0.01 to 1.

10. An ion exchange membrane, characterized in that: The fluorine-containing polymer comprises a fluorine-containing polymer obtained by the preparation method according to any one of claims 1 to 7 or a fluorine-containing polymer according to claim 8 or 9.

11. The ion exchange membrane according to claim 10, characterized in that The thickness of the ion exchange membrane is 5 to 450 μm; and / or, the ion exchange capacity of the ion exchange membrane is 0.1 to 4 mmol / g; And / or, the ion exchange membrane further comprises a reinforcement membrane, the reinforcement membrane is a porous membrane, and the material of the porous membrane comprises at least one of non-fluorinated polyolefin, fluorinated polymer material or aromatic polymer.

12. The method for preparing an ion exchange membrane according to claim 10 or 11, characterized in that: The following steps are involved: (a) dispersing a fluorine-containing polymer in a solvent to obtain a dispersion; (b) forming and drying the dispersion obtained in step (a) to obtain an ion exchange membrane.

13. The method for preparing an ion exchange membrane according to claim 12, characterized in that: In the step (a), the solvent comprises at least one of water, a high boiling point organic solvent, tetrahydrofuran, and a lower aliphatic alcohol; And / or, in the step (a), the dispersion temperature is 10 to 240° C., the dispersion time is 0.1 to 24 h, the dispersion pressure is normal pressure to 20 MPa, and the dispersion method includes at least one of stirring, shaking or ultrasound; And / or, in the step (b), the forming comprises at least one of casting, pouring or coating; And / or, in the step (b), the drying temperature is 20 to 180°C; And / or, the step (b) further comprises: coating the dispersion on one side or both sides of the reinforcement layer, and drying to obtain the ion exchange membrane.

14. Use of the ion exchange membrane according to claim 10 or 11 or the ion exchange membrane prepared by the preparation method according to claim 12 or 13 in batteries, chlor-alkali industry, water electrolysis hydrogen production, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.